The Dynamics of Convergence and Speed of Adjustments across Asia Pacific Equity Markets - Chong Hin, Chuah (2007)
Financial integration is one of the most important topics of studies in the recent years to investigate the characteristics of economics growth, as well as interest rates movements among different countries. Globalisation has intensified the interdependence and competition between economies in the world market. As a result, trading in goods and services and the movements of capital between countries has increased. With reference to the trend in capital market liberalisation, our research objectives focus on analysing the dynamics of financial convergenc and speed of adjustments ofthe stock markets capatalization in the Asia Pacific region. Our dissertation concluded that the standard deviation-growth rates characteristics of emerging Equity Market and Developed Market in Asia Pacific is growing in tandem. China, which is the member country of the Emerging Equity Market is experiencing exponential growth in its financial market. In fact, it is statistically significant that China is diverging from both the Emerging and Developed Equity Markets. China's rapid stock market capitalization growth in the recent years could be the results of financial and trade openness since a decade ago. The stock market capitalization growth rates of the 12 Asia Pacific Countries are shown to be cointegrated with the growth rates of stock market capitalization of Emerging Countries and Developed Equity markets, and their relationships can be specificed by an error correction representation, which also identify the process of growth rates adjustment towards a long-run equilibrium path. A country and a group of countries that conform to cointegration relationship are subjected to a common force of attractor and a leading growth rate influential role. The results indicate that China, Hong Kong SAR, Singapore, Australia, New Zealand and possible Malaysia play the leading countries role in the Developed Equity Market in paving the stock market capitalization growth path. These results support the view that stock market capitalization growth rates of different countries in Asia Pacific are linked together over time and their parallel fluctuation is not a matter of coincidence.